As formas de expressão do conservadorismo na política de assistência social e sua reprodução na prática profissional dos(as) assistentes sociais nos CRAS de João Pessoa-PB - Borba, Tiana de jesus (2015)
The dissertation proposes a discussion about the forms of expression of the conservatism in the professional practice of the social workers from the CRAS of João Pessoa-PB. The study has as a research subject the social workers that work in the Reference Center of Social Assistance (CRAS) of the municipality of João Pessoa, whose time frame is the year of 2015. The research is characterized for being of a qualitative and quantitative nature, grounded in theoretical sources of the critical-dialectical dimension, for the apprehension of the movement of the reality. We approach in this way the forms of expression of the conservatism, since its “classic” form until the contemporary versions, that renews and expand its expressions in the framework of the Basic Protection of Social Welfare Policy, because we believe that the professional practice is signed in conservative relations in the social welfare policy, which assume operational characteristics guided by intervention mechanisms that end up reproducing conservative traits that, in turn, serve segments of the ruling class. Thus the policy of social work reproduces the control of social relations, insofar as it emerges as “anti-poverty” compensatory programs, assuming a selective and fragmented character that merely minimizes the levels of impoverishment.